Applications of human factors approaches and methods to the development of teleconsultations in primary care: a systematic scoping review - Marion Bennie; Aimee Ferguson; Rosemary Newham; Emma Dunlop; Kate Preston (BMJ Open Quality)
Introduction Given the level of encouragement seen in recent policy, it is important to understand how teleconsultation technologies are designed, implemented and used in primary care settings to further encourage their use. Despite being an area of research warranting interest from the area of human factors, knowledge of the discipline’s application is scarce. This systematic scoping review aimed to identify human factors approaches and methods previously applied to the development of teleconsultation technologies in primary care.Methods Medline, Embase, PsycINFO, Ergonomics Abstracts and Engineering Village were searched for peer-reviewed articles. Included studies were published 2010 onwards, focused on the development of teleconsultation technologies in primary care and adopted an approach or method fitting within the domain of human factors. Key findings underwent a content analysis.Results 70 studies were identified, most published 2019 onwards. The review identified 20 human factors approaches, the majority of which were applied to evaluate the use of teleconsultations, with less focus on the design and implementation stages. A variety of data collection methods, theories, models and frameworks were found. Although the focus of all studies fits within the domain of human factors, none of the included studies referred to ‘human factors’ explicitly.Conclusions The findings illustrate approaches that have been applied when designing, implementing and evaluating the use of teleconsultations. Although the studies may not have intended to adopt a human factors lens, the approaches used relate to the wider discipline. Further analysis of the studies evaluating use could provide insight into how these technologies are being used and the factors influencing use.